Comparative fractal analysis of the heart rhythm variability among female biathletes with different training statuses - Bolotin, A.; Bakayev, V.; Bochkovskaya, V. (World Congress of Performance Analysis of Sport XII, 2018)
The paper notes a strict coherence between hormone and nerve regulation components of female biathletes` heart rhythm as primarily Indicative regarding the training status. Harmonization of both heart rhythm regulation components reveal the high adaptive features of athletes` bodies upon exertion. Obvious heart rhythm regulation components imbalance bespeaks the low exercise tolerance. By analyzing the female athletes` heart rhythm deviations, one can effectively assess their functional reserves and identify an adequate physical exertion throughout a training process.